LAJU INFILTRASI PADA BERBAGAI NAUNGAN DI KEBUN KOPI RAKYAT SUMBERMANJING WETAN - Adinda Ardana Reswari; Sugeng Prijono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Climate change in coffee cultivation is very influential and can disrupt the hydrological cycle, so shade planting is required. Planting vegetation on coffee fields can affect the infiltration rate. The infiltration rate is the amount of water per unit time that enters the soil surface. The purpose of this study was to determine the infiltration rate with various shading, namely mixed shade (sengon, teak, pepper, and coconut), sengon shade, and monoculture coffee land and to determine the relationship between soil physical properties and infiltration rate on people's land. The measurement of the infiltration rate was done with a double ring infiltrometer and the Horton model. Infiltration rate can be influenced by a variety of soil properties such as bulk density, soil pore distribution, soil aggregate stability, soil texture, soil organic matter content, and land use. The analysis used correlation, linear regression, multiple linear regression, and t-test. Differences in shade and soil properties affect the infiltration rate, especially micropores and soil porosity. Soil with a lot of micro-pore soil, low porosity and clay texture has a slow infiltration rate. The results of the t-test between the actual infiltration rate and the infiltration rate of the Horton model showed no significant difference; therefore, Â the Horton method approach can be used in estimating the actual infiltration rate in coffee fields.